The baking quality of soft winter wheat depending on the damage of grain by a bedbug-tortoise - Жемела, Г. П.; Бараболя, О. В. (Scientific Progress & Innovations, 2012)
The degree and the character of damage of soft winter wheat grain have been considered that worsens physical properties of grain: the masses of 1000 grains, natures, glassiness, amount and quality of gluten, bakery properties. It is the result of action of protease enzyme that is secreted by a bedbug-tortoise in the process of grain damage. The agrotechnical, biological and chemical methods of bedbug-tortoise control do not guarantee complete liquidation of its harmfulness. Method of inactivation of protease enzyme in the process of preparation of dough for baking bread due to the use of water solution (0,2-0,4%) of acetic acid provides the receipt of bakery qualities equal to undamaged grain that is used for preparation of flour and baking.